Internação compulsória e involuntária na compreensão de enfermeiros atuantes em saúde mental - Xavier, Mariane da Silva (2015)
The historical of the mental health has been marked by the discrimination, exclusion and removal of the persons with mental upset of the society. In this sense, one has like objective, to analyses the understanding of active nurses in mental health about the compulsory admissions and involuntary proposals for the Law of the Brazilian Psychiatric Reform. It is the question of an exploratory-descriptive inquiry with qualitative approach carried out in unities of psychiatric admission in general hospitals and services substitutive in the area of mental health of the Only System of Health in the local authority of Saint Maria. The data collection took place of March to May of 2014, through interview semi-structured with open question, developed in individual and carved form, in a room reserved in the above-mentioned services with eight active nurses in mental health. For so much, the next question happened: which his understanding of compulsory and involuntary admission? The data were subjected to the Analysis of Content and 7.0 (Qualitative Research and Solutions) organized with help of the Software Atlas You, it was inspired in the theoretical referential system of Paulo Amarante. They were respected all the aspects ethical of the inquiries with human beings ruled in the Resolution N. 466 of 2012 of the National Council of Health. Of the analysis of the finds from the reading of the content of the interviews, two categories surfaced: compulsory and involuntary admissions: understanding of the active nurses in mental health; and, compulsory and involuntary admission in the professional daily life of the active nurse in mental health. The results showed up that the nurses understand the compulsory and involuntary admissions as something that must be seen besides the disease, since social, economic, familiar factors when they are in imbalance can bring in an admission. They understand that the Law of the Psychiatric Reform brought changes in the presence in mental health, however it is still not totally in accordance with the ideals of the Law, since the changes are situated more specifically in the services without reaching the community, being the fragmentation of the Net of Attention Psychosocial one of the challenges so that the ideal is reached. Another challenge pointed by the nurses there are the readmissions for the precarious adherence of the users to the services substitutive. Besides, the nurses try to establish a communication with the judicial thing in an attempt of reducing the compulsory admissions. The nurses can differentiate the different types of admission, being that the compulsory and involuntary admissions from the understanding of the nurses do not appear effective, but in crisis situations there are still the most used resource. Between the feelings that these two types of admission wake in the nurses they are the satisfaction feeling when they manage to avoid the admissions and it of frustration when they do not manage. It is ended that so that there is a desinstitucionalização, besides the constitution of a Net of Attention continuous and resolute Psychosocial it is necessary to surpass the readmissions that produce the so-called phenomenon revolving-door.